Macchine leibniziane? - Marrone, Pierpaolo (Filosofia, 2020)
Are robots capable of forming concepts? The problem can be addressed starting from a similar question, namely that relating to the possibility that animals are recognized as capable of forming concepts. Different positions have been addressed on this issue. A profitable possibility of analysis is offered by Davidson’s skeptical position in his influential Rational Animals. I examine some of the objections made to the position that denies that animals can form concepts. I affirm that none of these are conclusive and I draw the idea that if the ability to form concepts must be recognized to animals, then the same position must also be supported with respect to robots.